2024
DOI: 10.3390/ijms25021136
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Biomarkers for Parkinson’s Disease: How Far from Clinical Translation?

Alice Gualerzi,
Silvia Picciolini,
Marzia Bedoni
et al.

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder affecting about 10 million people worldwide with a prevalence of about 2% in the over-80 population. The disease brings in also a huge annual economic burden, recently estimated by the Michael J Fox Foundation for Parkinson’s Research to be USD 52 billion in the United States alone. Currently, no effective cure exists, but available PD medical treatments are based on symptomatic prescriptions that include drugs, surgical approaches and rehabilitation tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…(1) Participants included all PD patients diagnosed with PD regardless of factors such as stage, or presence of dementia. (2) The interventions reviewed in this study included evaluations of protein or miRNA PD biomarkers in exosomes in blood samples. (3) The comparator to PD patients was healthy controls.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…(1) Participants included all PD patients diagnosed with PD regardless of factors such as stage, or presence of dementia. (2) The interventions reviewed in this study included evaluations of protein or miRNA PD biomarkers in exosomes in blood samples. (3) The comparator to PD patients was healthy controls.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Additionally, several studies have demonstrated elevated levels of α-syn in plasma neuronal-derived exosomes from PD patients compared to healthy controls [32,38,51,95]. It was reported that the interaction between α-syn and membranes plays a significant role in the conformational shifts of α-syn, potentially impacting protein functionality and contributing to aggregation in PD progression [2]. Furthermore, the aggregated and harmful variant of the protein, oligomeric α-syn, has been observed to engage with lipids, inducing structural alterations in lipid membranes.…”
Section: Meta-analysis On Total Exosomal and Neuron-derived Exosomal ...mentioning
confidence: 99%
See 2 more Smart Citations